Is moral bioenhancement dangerous?. Issue 1 (9th November 2015) - Drake, Nicholas
Abstract : In a recent response to Persson and Savulescu's Unfit for the Future, Nicholas Agar argues that moral bioenhancement is dangerous. His grounds for this are that normal moral judgement should be privileged because it involves a balance of moral subcapacities; moral bioenhancement, Agar argues, involves the enhancement of only particular moral subcapacities, and thus upsets the balance inherent in normal moral judgement. Mistaken moral judgements, he says, are likely to result. I argue that Agar's argument fails for two reasons. First, having strength in a particular moral subcapacity does not necessarily entail a worsening of moral judgement; it can involve strength in a particular aspect of morality. Second, normal moral judgement is not sufficiently likely to be correct to be the standard by which moral judgements are measured.